Pengembangan Desa Wisata Kampung Ekologi Temas Kota Batu Jawa Timur - Khoirunnisa, Ninin ; Mutiara, Farah (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
Tourism is one of the services and services industry activities that are Indonesia's mainstay in order to increase the country's foreign exchange. In the City of Stone Tourism the tourism sector has become a superior potential capable of supporting regional income. This study aims to determine the efforts made by the local government and tourism village administrators, knowing the driving factors, inhibiting factors and strategies in the development of Kampung Tourism Villages. This research is descriptive research with the support of qualitative data. Data collection techniques were obtained through in-depth interviews and documentation studies. Determination of informants was obtained by purposive sampling technique. Like the Head of Tourism and Culture Marketing, Community Empowerment and Temas Village Development, General Chairman of Batu Ecology Village, Chair of the Batu Ecology Village Development Division and local community / Batu Ecology Village manager. Data analysis techniques using interactive analysis. From the results of the study, it was found that the development of rural tourism by the Department of Tourism and Culture of Batu City, with the concept of outward linkages, and inward (backward linkages). Efforts are made starting from inventorying the potential of tourism villages, making tourism service facilities, promoting and developing facilities that support tourist villages.